Climate Change Analysis for Bangladesh Using CMIP5 Models (The Dhaka University Journal of Earth and Environmental Sciences, 2021)
Using the Coupled Model Inter-comparison Project phase 5 (CMIP5) global climate modeling predictions, the study analyzes the distribution of rainfall and temperature in Bangladesh in recent years (1981–2005) and in three future periods (2025–2049, 2050–2074 and 2075–2099) considering RCP 4.5 and RCP 8.5 scenarios. In the historical period, all three CMIP5 models (MPI-ESM-LR, MPI-ESM-MR and NorESM1-M) mostly underestimated the observed mean rainfall data collected from Bangladesh Meteorological Department (BMD), but for temperature the result is found almost similar between models and observation. The CMIP5 models simulation reveal biases in monthly mean rainfall and temperature over Bangladesh in the past, so bias-correction is performed for future data. Quantile mapping bias-correction reduces significant amount of biases from the projection data of rainfall and temperature. By the end of the twenty-first century, the multi-model ensemble annual mean rainfall averaged over Bangladesh is projected to change between -2% to 9% and -3% to 15% under RCP 4.5 and RCP 8.5, respectively. The changes in spatial patterns of annual rainfall indicate a decrease in rainfall over a major portion in the west and the northwestern and an increase in the southeast, east, and the northeastern part of the country. The multi-model ensemble projection reveals a continuous increase in the annual mean temperature and shows a larger increase over the northwestern part and west-central part of Bangladesh. By the end of the twenty-first century, the annual mean temperature over Bangladesh is projected to increase by 1.9 (0.9-2.8) °C and 4 (2.8-4.6) °C under the RCP 4.5 and RCP 8.5 scenarios respectively, relative to the reference climate (1981-2005).The Dhaka University Journal of Earth and Environmental Sciences, Vol. 9(1), 2020, P 1-12